Africanizing Anthropology : Fieldwork, Networks, and the Making of Cultural Knowledge in Central Africa - Schumaker, Lyn (Book collections on Project MUSE., 2001)
An innovative cultural study of a major site of British anthropology, done with methods from the history of science, detailing the development of methods, practices, and work culture in the colonial context.